Impact of Socio-Economic Status on Educational and Career Aspirations of Grade 10 Maguindanaon Students at Esperanza National High School - Elsie C. Laroco (RIRAI Publisher, 2022)
Decision-making process relative to educational and career aspirations has a very significant part in planning career guidance which helps the students to effectively choose the career track/strand in senior high school curriculum. This study aimed to investigate the influence of socio-economic status of students on their educational and career aspirations. Descriptive correlational research design was employed in which a researcher-made checklist was answered by the randomly chosen Grade 10 Maguindanaon students. Frequency, percentage and Chi-square were appropriately applied to provide good inferences and implications of the results. Findings revealed that most of the parents of Grade 10 Maguindanao students finished high school level. Majority of the fathers were farmers and the mothers were housekeepers whose combined monthly income ranged from ₱10,000 to ₱15,000. Socio-economic status of Maguindanao students was significantly related to their educational and career aspirations. Higher social standing of the parents led to the higher educational and career aspirations. Low family income hampered the students to take up career track with high standard. Thus, Esperanza National High School should initiate an intervention program to inspire Maguindanaon students to pursue their educational and career aspirations despite of the financial woes they experience in life.